ENHANCED EFFICIENCY OF DYE-SENSITIZED SOLAR CELLS USING ZNO NANOPARTICLE DOPING CU FROM PINEAPPLE PEEL EXTRACT WITH MODIFIED NATURAL DYE SOLUTION - Rohmawati, L.; Ferdianto, S.P.; Ma’arif, M.S.; Ardiansyah, F.F.; Muadhif, F.I.; Setyarsih, W.; Supardi, Z.A.I.; Darminto, D. (Eurasian Physical Technical Journal, 2025)
Photoanodes and dye solutions are indispensable in the stability and efficiency of Dye-Sensitized Solar Cells’ performance. In this study, the photoanode uses a ZnO sample doped with Cu, made using a green synthesis technique with bio-reduction from pineapple skin extract. Meanwhile, using the maceration method, the dye solution is made from mulberry fruit extract and moringa leaves. For Dye-Sensitized Solar Cells applications, ZnO photoanodes doped with 1%, 3%, 5%, and 10% Cu were each depleted on ITO glass and immersed in the dye solution for one day. The results were then tested for electrical conductivity and performance in Dye-Sensitized Solar Cells. Adding Cu doping concentration to the ZnO photoanode can affect the performance of the Dye-Sensitized Solar Cell. In this work, the ZnO sample doped with 5% Cu as a photoanode showed the highest efficiency at 1.67% with an electron lifetime of 12 ms, compared to the photoanode without Cu doping or with Cu doping at concentrations of 1%, 3%, and 10%. Thus, Cu-doped ZnO nanoparticles and dye solutions from natural materials can be further developed for Dye-Sensitized Solar Cells applications.